Morphological and molecular identification of holothuria (Merthensiothuria) leucospilota and stichopus horrens from Pangkor Island, Malaysia - Kamarudin K.R.; Maryam Mohamed Rehan (Universiti Sains Malaysia Press, 2024)
Indexed by Scopus